Mechanically flexible pentadienenitrile derivative-based molecular crystals exhibiting distinct photoresponsive behavior - Thanasekar, Vishnukumar; Bhowmik, Aritra; Mishra, Manish Kumar; Ghosh, Soumyajit (Crystal Growth & Design, 2026)
Photoresponsive molecular crystals constitute an emerging class of functional crystalline smart materials that have garnered considerable attention due to their capacity to convert light energy into mechanical motion. These light-induced responses, known as photomechanical effects, render these crystals promising candidates for advanced photoactuators, photonic devices, and intelligent materials. In this study, we synthesized two novel diphenylpenta-2,4-dienenitrile derivative-based crystals 1 and 2, which demonstrate mechanical flexibility and distinct photomechanical responses to 420 nm LED irradiation. Notably, crystal 1 exhibited sequential bending, initially away from the light source and subsequently toward it upon prolonged exposure, whereas crystal 2 exhibited photosalient breaking. These divergent responses are attributed to [2 + 2] photocycloaddition reactions occurring within the crystal lattice. The variations in kinematic behavior are ascribed to differences in the accumulation and subsequent release of strain energy during photocycloaddition. The synergistic integration of photomechanical activity and mechanical flexibility underscores the multifunctional nature of these materials, offering critical insights for the design of crystals with potential applications in optoelectronics, photonics, and molecular switches, thereby expanding the scope of future photoresponsive organic materials.